Utilization of undeveloped jackfruit perianth as filler in skinless longganisa - Lazo, Candice Kaye B.
ABSTRACT This study was conducted to utilize undeveloped jackfruit perianth as meat filler in skinless longganisa . The formulation used was chosen from three published formulations which were subjected to consumer acceptance t est. In the most acceptable formulation, perianth was used to replace 10%, 30%, and 50% of the lean meat content. The samples were subjected to physico - chemical ( i.e., cooking yield, water - holding capacity, compactness, and shrinkage) , proximate ( i.e., moi sture, crude fat, and crude fiber contents ), and microbiological (i .e., total plate count and coliform c ount ) tests. Likewise, consumer acceptance test using 50 randomly selected untrained panelists was done. The selected formulation for the perianth - fille d skinless longganisa was standardized. The Bureau of Animal Industry ( BAI ) formulation, characterized with 70% lean meat and 30% back fat content, was regarded as the most acceptable skinless longganisa formulation. The results of the physico - chemical, p roximate, microbiological, and consumer acceptance tests revealed that the amount of perianth which can be used as filler in skinless longganisa was 30%. Moreover , the formulation used w as able to come up with a standardized and safe skinless longganisa . It was concluded from this study that undeveloped jackfruit perianth can be incorporated as meat filler in skinless longganisa by as much as 30%.